Biostimulants in Agriculture: Benefits and Applications - Kumari, Megha; Singh, Teekam; Devi, Ayekpam Dollina (Chronicle of Bioresource Management, 2023)
Biostimulants play a crucial role in modern agriculture by enhancing plant growth, improving stress tolerance, and promoting soil health. Unlike traditional fertilizers and pesticides, they stimulate natural physiological processes, leading to better nutrient absorption, increased crop yield, and improved quality. Biostimulants include various substances such as humic acids, seaweed extracts, protein hydrolysates, arbuscular mycorrhizal fungi, plant growth-promoting rhizobacteria, and silicon, each contributing uniquely to plant development. Their application supports sustainable farming by reducing chemical dependency and mitigating the effects of environmental stress.